Geology of Lonar Crater, India - Maloof, A. C.; Stewart, S. T.; Weiss, B. P.; Soule, S. A.; Swanson-Hysell, N. L.; Louzada, K. L.; Garrick-Bethell, I.; Poussart, P. M. (Geological Society of America Bulletin, 2010)
Lonar Crater, India, is one of the youngest and best preserved impact structures on Earth. The 1.88-km-diameter simple crater formed entirely within the Deccan traps, making it a useful analogue for small craters on the basaltic surfaces of the other terrestrial planets and the Moon. In this study, we present a meter-scale-resolution digital elevation model, geological map of Lonar Crater and the surrounding area, and radiocarbon ages for histosols beneath the distal ejecta. Impact-related deformation of the target rock consists of upturned basalt flows in the upper crater walls and recumbent folding around rim concentric, subhorizontal, non-cylindrical fold axes at the crater rim. The rim-fold hinge is preserved around 10%-15% of the crater. Although tearing in the rim-fold is inferred from field and palcomagnetic observations, no tear faults are identified, indicating that large displacements in the crater walls are not characteristic of small craters in basalt. One significant normal fault structure is observed in the crater wall that offsets slightly older layer-parallel slip faults. There is little fluvial erosion of the continuous ejecta blanket. Portions of the ejecta blanket are overlain by aerodynamically and rotationally sculpted glassy impact spherules, in particular in the eastern and western rim, as well as in the depression north of the crater known as Little Lonar. The emplacement of the continuous ejecta blanket can be likened to a radial ground-hugging debris flow, based on the preserved thickness distribution of the ejecta, the efficient exchange of clasts between the ejecta flow and the underlying histosol, and the lack of sorting and stratification in the bulk of the ejecta. The ejecta profile is thickened at the distal edge and similar to fluidized ejecta structures observed on Mars.
id: 1846; 539YI Times Cited:0 Cited References Count:100Y